Delivering tele-chairwork: A qualitative survey of expert therapists. (3rd October 2021) - Pugh, Matthew; Bell, Tobyn; Dixon, Alison
Abstract: Objective: Recent years have seen a significant and rapid increase in the provision of tele-therapies. Chairwork methods such as empty-chair dialogues and role-play represent a "common" category of therapeutic interventions which are utilized in many psychotherapeutic approaches. However, guidelines for facilitating chairwork in tele-therapy are currently lacking. The aim of this study was to survey expert providers regarding how chairwork is best provided in internet-delivered psychotherapy. Method: Forty one experts were recruited from a range of therapeutic backgrounds including cognitive behaviour therapy, compassion focused therapy, emotion focused therapy, psychodrama, schema therapy, and voice dialogue. Participants completed a brief questionnaire survey exploring the delivery of tele-chairwork. Responses were analysed using thematic analysis. Results: Five themes were identified: (i) divided opinion; (ii) convergence between therapy and home; (iii) disconnection and depth; (iv) practical impediments and benefits; and (v) revising and re-visioning chairwork. Overall, results indicate that chairwork can be successfully incorporated into tele-therapy, but requires adaption and special considerations. Discussion: Despite challenges, tele-chairwork appears to be a feasible method of psychotherapeutic intervention. Preliminary guidelines for initiating, facilitating, and concluding tele-chairwork are presented, alongside future directions for research.